2017
DOI: 10.1007/s00232-017-9984-8
|View full text |Cite
|
Sign up to set email alerts
|

Oxysterols Versus Cholesterol in Model Neuronal Membrane. I. The Case of 7-Ketocholesterol. The Langmuir Monolayer Study

Abstract: Oxysterols are products of cholesterol oxidation. They can be formed endogenously (in both enzymatic and non-enzymatic reactions) as well as exogenously (delivered with food). Recent studies clearly demonstrate cytotoxic properties of these compounds, being mainly due to their incorporation into natural lipid bilayers. This process can influence mechanical and physicochemical properties of biomembrane—mainly by modifying the interactions between its components, which may result in the disruption of proper func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…The results of surface pressure ( ) and electric surface potential changes ( ) versus area per molecule ( ) measurements for the investigated lipids are presented in Figure 1 and Figure 2 . Experimental isotherms for all the studied phospholipids are in good agreement with those already published ([ 33 ] for DPPC, [ 34 ] for DSPC, [ 35 ] for DAPC, [ 36 ] for DOPC, [ 37 ] for DPPE and [ 38 ] for SM). Experimental curves can be characterized by two important parameters: critical area ( , which corresponds to the area at which is triggered off) and maximum value of surface potential ( ).…”
Section: Resultssupporting
confidence: 87%
“…The results of surface pressure ( ) and electric surface potential changes ( ) versus area per molecule ( ) measurements for the investigated lipids are presented in Figure 1 and Figure 2 . Experimental isotherms for all the studied phospholipids are in good agreement with those already published ([ 33 ] for DPPC, [ 34 ] for DSPC, [ 35 ] for DAPC, [ 36 ] for DOPC, [ 37 ] for DPPE and [ 38 ] for SM). Experimental curves can be characterized by two important parameters: critical area ( , which corresponds to the area at which is triggered off) and maximum value of surface potential ( ).…”
Section: Resultssupporting
confidence: 87%
“…Oxysterols are present at very low levels compared to cholesterol (Wnętrzak et al, 2017), and alterations of cholesterol synthesis or trafficking are induced by the loss of function of several genes responsible for HSP. For example, loss of function of Erlin1 and Erlin2, mutated in SPG62 and SPG18, respectively, are responsible for early onset autosomal recessive HSP associated with cognitive impairment (Alazami et al, 2011;Novarino et al, 2014).…”
Section: Alteration Of Cholesterol Synthesis or Trafficking In Hspmentioning
confidence: 99%
“…Additionally, synthetic 24­( R )-OH is at least 1 order of magnitude less active compared to the natural isomer . Previous investigations involving oxysterols revealed that not only the kind of an additional polar group introduced into the cholesterol backbone , but also its position in the sterane system or chain and molecule orientation , strongly effect oxysterol organization at the phase boundary and modify the interactions with other lipids. This may directly impact the membranous activity of oxysterols as well as their other biological properties.…”
Section: Introductionmentioning
confidence: 99%